PROMOTING LEADERSHIP IN PUBLIC HEALTH - Zulkifli b Ahmad (Malaysian Journal of Public Health Medicine, 2004)
In times of great health challenges in the global environment today, public health leadership is crucial quality for many of us. The challenges brought on by globalisation, poverty, disparities between the developed and the developing world, increasing social inequities, new and re-emerging diseases poses acquiring new skills and knowledge to overcome them. We, as leaders in Public Health, need to unleash the full potential, productivity, motivation and commitment of those working under us. This is more acute in times when Public Health in Malaysia suffers some degree of lower m01'ale due to poorer promotional prospects, lack of recognition as a specialist and the allowance due and the current lack of training opportunities.